Respuesta :

Lanuel

Based on the calculations, the formula of this sinusoidal function is equal to f(x) = 6cos(2x) + 4.

How to write the formula of this function?

Mathematically, the standard equation of a cosine function is given by:

y = Acos(Bx - C) + D

Where:

  • A is the amplitude.
  • B = 2π/P.
  • P is the period.
  • C is the phase shift.
  • D is the center line (midline).

For the amplitude, we have:

A = maxline - midline

A = 10 - 4

Amplitude, A = 6.

Since the maxline to the midpoint is euqal to π/4, we have:

¼ × P = π/4

4P = 4π

P = π

For the value of B, we have:

B = 2π/P

B = 2π/π

B = 2.

Since there isn't any phase shift, the value of C is equal to zero (0) and D is equal to 4.

Next, we would substitute the parameters into the cosine function:

y = Acos(Bx - C) + D

y = 6cos(2x - 0) + 4

f(x) = y = 6cos(2x) + 4.

Read more on cosine function here: https://brainly.com/question/26993851

#SPJ1